2002
DOI: 10.1021/es011255v
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Aromatic Substitution Reactions of Chloroazines with Bisulfide (HS-) and Polysulfides (Sn2-)

Abstract: Reactions of bisulfide and polysulfides with chloroazines (important constituents of agrochemicals and textile dyes) were examined in aqueous solution at 25 degrees C. For atrazine, rates are first-order in polysulfide concentration, and polysulfide dianions are the principal reactive nucleophiles; no measurable reaction occurs with HS-. Second-order rate constants for reactions of an array of chloroazines with polysulfides are several orders of magnitude greater than for reactions with HS-. Transformation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 50 publications
2
78
0
Order By: Relevance
“…The same products were also obtained in one previous study, which identified the polysulfur-substituted products in the nucleophilic reaction of chloroacetaminlide herbicides with polysulfides (S n 2À ) [13]. The nature of the dechlorinated products substituted by nucleophiles suggests the bimolecular nucleophilic substitution (S N 2) mechanism being mainly responsible for metolachlor transformation by bisulfide [41], and the aluminas acting as the solid-mediator for accelerating the reactions between metolachlor and nucleophiles of bisulfide in the heterogeneous system [42,43].…”
Section: Products Of Metolachlor Transformation By Bisulfide On Aluminassupporting
confidence: 74%
“…The same products were also obtained in one previous study, which identified the polysulfur-substituted products in the nucleophilic reaction of chloroacetaminlide herbicides with polysulfides (S n 2À ) [13]. The nature of the dechlorinated products substituted by nucleophiles suggests the bimolecular nucleophilic substitution (S N 2) mechanism being mainly responsible for metolachlor transformation by bisulfide [41], and the aluminas acting as the solid-mediator for accelerating the reactions between metolachlor and nucleophiles of bisulfide in the heterogeneous system [42,43].…”
Section: Products Of Metolachlor Transformation By Bisulfide On Aluminassupporting
confidence: 74%
“…Polysulfides play an important role in numerous environmental processes due to their high reductive and nucleophilic reactivity. Among those processes are transition metal complexation and pyrite formation (Rickard 1975;Howarth 1979;Luther 1991;Paquette and Helz 1997;Chadwell et al 1999;Luther and Rickard 2005), thiosulfate production by disproportionation to sulfide and thiosulfate under basic conditions (Bloxam 1895;Giggenbach 1974;Licht and Davis 1997), sulfurization of sedimentary organic matter (Aizenshtat et al 1983;Kohnen et al 1989;Vairavamurthy and Mopper 1989;Vairavamurthy et al 1992;Krein and Aizenshtat 1993;Aizenshtat et al 1995;Amrani and Aizenshtat 2004), volatile sulfur compounds (VSCs) formation (Ginzburg et al 1999;Heitz et al 2000;Franzmann et al 2001;Kamyshny et al 2003), as well as reductive dehalogenation and nucleophilic substitution of organo-halogen pollutants (Roberts et al 1992;Perlinger et al 1996;Miller et al 1998;Lippa and Roberts 2002;Loch et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among the other nucleophiles whose reactions with pesticide compounds may be significant in the hydrologic system, perhaps the most important are reduced sulfur anions (Barbash and Reinhard, 1989a), particularly bisulfide, polysulfides (e.g., Barbash and Reinhard, 1989b;Lippa and Roberts, 2002;Loch et al, 2002;Miah and Jans, 2001;Roberts et al, 1992;Stamper et al, 1997), and thiosulfate (e.g., Ehrenberg et al, 1974;Wang et al, 2000). Reactions with these nucleophiles are often an indirect mechanism of biotransformation, as these and other reduced sulfur anions are derived primarily from biological activity.…”
Section: Neutral Reactionsmentioning
confidence: 99%
“…Such calculations have, in turn, been shown to be useful for elucidating the effects of pesticide structure on reactivity (e.g., Katagi, 1992;Lippa and Roberts, 2002).…”
Section: Structure and Properties Of Other Reactantsmentioning
confidence: 99%
See 1 more Smart Citation